KETERSEDIAAN WASTAFEL PORTABLE DI UNIVERSITAS CENDERAWASIH SELAMA PANDEMI COVID-19 - Johni Jonatan Numberi Numberi; Bernathius Julison; Apolo Safanpo; Marthen liga; Patrick Fandy; David Mangallo; Eka Irianto Bifnitme; Theresia Wuri; Helen Wayangkau; Annisa Novita Sari (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2021)
Abstract In order to implementing the 5 health protocols (washing hands, wearing masks, keeping distance, staying away from crowds and reducing mobility) during the current COVID-19 pandemic, the Chancellor of Cenderawasih University issued a circular stating that hand washing equipment on campus must be available as soon as possible and in sufficient quantity. Responding to the circular, the Faculty of Engineering, University of Cenderawasih formed a team to produce 7 units of Portable Wash Basin. The seven units are placed in the office of the Chancellor of Cenderawasih University and the Dean of Engineering Faculty. When producing Portable Wash Basin, the team involved several students. Student involvement is deemed necessary, so that students can produce their own Portable Wash Basin. The ability to produce these Portable Wash Basin is expected to be a driving force for students to become entrepreneurs. Abstrak Dalam rangka melaksanakan protokol kesehatan 5M (mencuci tangan, memakai masker, menjaga jarak, menjauhi kerumunan dan mengurangi mobilitas) pada masa pandemi COVID-19 sekarang ini, Rektor UniversitasCenderawasih menerbitkan surat edaran yang menyatakan bahwa alat pencuci tangan di lingkungan kantor universitas harus tersedia dalam jumlah yang cukup. Menanggapi surat edaran tersebut, maka Fakultas Teknik Universitas Cenderawasih membentuk suatu tim untuk memproduksi 7 unit alat cuci tangan Wastafel Portable. Ketujuh unit tersebut diletakkan di sekitar lingkungan kantor Rektorat Universitas Cenderawasih dan Dekanat Fakultas Teknik. Pada saat memproduksi alat cuci tangan tersebut, tim melibatkan beberapa mahasiswa. Keterlibatan mahasiswa dipandang perlu, agar selanjutnya mahasiswa yang bersangkutan dapat memproduksi sendiri Wastafel Portable tersebut. Kemampuan untuk memproduksi alat tersebut diharapkan dapat menjadidorongan agar mahasiswa mau berwirausaha.